Effect of Pulsed Photon Processing in Nitrogen Ambient on Optical and Electrophysical Characteristics of Silicon Dioxide Layers of Its Boundaries with Silicon - N. S. Kovalchuk; V. A. Pilipenko; Ja. A. Solovjov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The influence of pulsed photon processing in a nitrogen medium with an incoherent radiation flux from quartz halogen lamps directed to the non-working side of the wafer, providing heating to 1150 °C in about 7 s, on the optical properties of 17.7 nm thick silicon dioxide layers formed by pyrogenic oxidation of silicon doped with boron with the orientation (100), and on the electrophysical characteristics of the interface with silicon was established using the methods of infrared Fourier spectrometry, spectral ellipsometry, time-of-flight mass spectroscopy of secondary ions, and studies of the current-voltage and capacitance-voltage characteristics. It was revealed that pulsed photon processing of silicon dioxide layers leads to compaction and rearrangement of its structure, as well as to the formation of Si‒N bonds in silicon dioxide, providing nitridation of SiO2. This is indicated by the shift, decrease in the half-width and voltage of the main absorption band of the Si‒O bond, decrease in the refractive index from 1.48 to 1.47 and increase in the layer thickness to 18.2 nm. It is shown that nitridation of SiO2 layers during pulsed photon processing in a nitrogen atmosphere leads to a decrease in the leakage current of the dielectric by four times and its charge density by 3.43 times. This is 2.19 and 3.01 times more, respectively, than during processing in natural atmospheric conditions due to the formation of a layer with an increased nitrogen concentration at the Si–SiO2 boundary. The results obtained can be used to create dielectric coatings in electronic products.